ANALISIS TINGKAT EMISI GAS RUMAH KACA CO2-e DARI SAMPAH KOTA PEKANBARU UNTUK PENGEMBANGAN MODUL KONSEP ISU LINGKUNGAN PADA MATA KULIAH PENDIDIKAN LINGKUNGAN - Widie Kemala Hapsari; Sri Wulandari; Suwondo ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research was to determine the level of greenhouse gas emissions CO2-e from waste the city of Pekanbaru and develop modular concept of environmental issues in the subject of Environmental Education among October 2015 until January 2016. The results from this research used to develop module unit subjects Environmental Education. This research did by 2 phases: analysis of greenhouse gas emissions and the development stage modules. Research use descriptive methode. The data collection did by using survey methods to make observations in the Muara Fajar landfill . Sampling done by random sampling, to took rubbish out of three trucks at Muara Fajar landfill as much as 500 liters container sizes daily until 8 days. The calculation of greenhouse gas emissions CO2-e by using data analysis methods FOD (first order decay) at the level of accuracy of Tier 1. The parameters in this study is a waste composition, type of waste, the level of greenhouse gas CO2-e and types of plants in the buffer zone in Muara Fajar landfill. The results of survey revealed that the greenhouse gas emissions of CO2-e from of the span of 5 years of 21.7 %. and highest in 2014 amounted to 67.832 tonnes of CO2-e, with an average increase of emissions by 26.5%. The results of the study can be used as a modular unit concept of environmental issues in the subject of Environmental Education.Key Words: Greenhouse gas CO2-e emission, module, waste of Pekanbaru City